CLINICAL CHARACTERISTICS OF WOMEN REFERRED TO CARDIAC SPECT: WHEN AND WHO? DATA FROM LATVIAN CARDIAC SPECT REGISTRY. (June 2022) - Vitola, Barbara; Mintale, Iveta; Trusinskis, Karlis; Kalnina, Marika; Kedrova, Jelena; Erglis, Andrejs
Abstract : Objective: Population based cross-sectional study of cardiovascular risk (CVR) factors in Latvia from year 2009 till 2019 revealed that women in age 25 -74 are in a very high CVR group: 61% of women have dyslipidemia, more than 33% have arterial hypertension (AH) and 28% are overweight. The data indicates the necessity for focused diagnostics and early detection of cardiovascular disease. The aim of study was to define the clinical profile and risk factors for women with suspected coronary artery disease (CAD) reffered to cardiac single photon emission computed tomography (SPECT) in Latvia and to find out the correlation between nuclear test result and patient clinical presentation. Design and method: Cardiac SPECT was performed in a single centre from 2018 till 2021. The women patients were analyzed by risk factors and previous diagnosis of CAD. Exercise test was performed in all cases. Patients were divided into 2 groups: normal myocardial perfusion or true myocardial perfusion defect, defined as area of ischemia more than 10% of the left ventricle myocardium mass. Results: 726 SPECT data were analyzed. The mean age of women patients was 62.6 ± 10.6 years. More than half of the patients (n = 486, 66.9%) were overweight (BMI> 25.0 kg/m2) and 33.3%(n = 242) were obese (BMI> 30.0 kg/m2). 87 (11.9%) women were current or ex-smokers. Dyslipidemia was present in in 614 (84.6%), AH in 535 (73.7%) and type 2 Diabetes mellitus (T2DM) in 60 (8.3%) patients. 104 (14.3%) patients were asymptomatic, but with intermediate to high pre-test probability for CAD. Known CAD was present in 298 (41.0%) patients. Exercise test was found positive in 306 (42.1%) patients and the test result was not always associated with ischaemia in SPECT (p = 0.063). True myocardial perfusion defect was detected in 125 patients (17.2%). Correlation was found between significant perfusion defect in SPECT and risk factors - AH (p = 0.013) and dyslipidemia (p = 0.029). Conclusions: The registry proves the high value of imaging with cardiac SPECT for diagnostics of CAD. Women patients with intermediate or high pre-test probability – even asymptomatic or with non informative exercise test should be reffered for cardiac SPECT.